Automatic Detection of High-Frequency Oscillations With Neuromorphic Spiking Neural Networks - Burelo, Karla; Sharifshazileh, Mohammadali; Indiveri, Giacomo; Sarnthein, Johannes (Frontiers in Neuroscience, 2022)
Interictal high-frequency oscillations detected in electroencephalography recordings have been proposed as biomarkers of epileptogenesis, seizure propensity, disease severity, and treatment response. Automatic high-frequency oscillations detectors typically analyze the data offline using complex time-consuming algorithms, which limits their clinical application. Neuromorphic circuits offer the possibility of building compact and low-power processing systems that can analyze data on-line and in real time. We have designed a fully automated high-frequency oscillations detection pipeline using, for the first time, spiking neural networks and neuromorphic technology. We demonstrated that our high-frequency oscillations detection pipeline can be applied to recordings from different modalities (intracranial electroencephalography, electrocorticography, and scalp electroencephalography) and showed that it can be implemented in our custom-designed neuromorphic processor. Our high-frequency oscillations detection method resulted in high accuracy and specificity in the prediction of seizure outcome in patients implanted with intracranial electroencephalography and electrocorticography, and in the prediction of epilepsy severity in patients recorded with scalp electroencephalography. Our research provides a further step towards the real-time detection of high-frequency oscillations using a compact and low-power neuromorphic device. The real-time detection of high-frequency oscillations in the operation room may improve the seizure outcome of epilepsy surgery, while the use of our neuromorphic processor for non-invasive therapy monitoring might allow for more effective medication strategies to achieve seizure control. Therefore, our system has the potential to improve the quality of life in patients with epilepsy by improving epilepsy diagnostics and treatment.